2018
DOI: 10.1029/2017ja024798
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Crustal Magnetic Field Control of Ions Precipitating Into the Upper Atmosphere of Mars

Abstract: We present the effects of the local magnetic field configurations on ions precipitating into the upper atmosphere of Mars using Mars Atmosphere and Volatile EvolutioN (MAVEN) observations. Precipitating pickup planetary heavy ions (O + , O + 2 , and CO + 2 ) are of particular interest in the Martian plasma environment because they potentially enhance the sputtering loss of ambient neutral particles. In addition, solar wind protons (and H + pickup ions) penetrate into the dayside atmosphere due to the direct in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 59 publications
(81 reference statements)
3
31
2
Order By: Relevance
“…As an example, Hara et al (2018) and Hara et al (2017) have shown that large variation of the precipitating flux can be expected in correlation with the solar wind pressure, the orientation of the electric field of convection, and with the presence of crustal magnetic fields. As an example, Hara et al (2018) and Hara et al (2017) have shown that large variation of the precipitating flux can be expected in correlation with the solar wind pressure, the orientation of the electric field of convection, and with the presence of crustal magnetic fields.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, Hara et al (2018) and Hara et al (2017) have shown that large variation of the precipitating flux can be expected in correlation with the solar wind pressure, the orientation of the electric field of convection, and with the presence of crustal magnetic fields. As an example, Hara et al (2018) and Hara et al (2017) have shown that large variation of the precipitating flux can be expected in correlation with the solar wind pressure, the orientation of the electric field of convection, and with the presence of crustal magnetic fields.…”
Section: Resultsmentioning
confidence: 99%
“…The first evidence of heavy ion precipitation for nominal solar wind conditions has been reported by Leblanc et al (2015), highlighting that sputtering should clearly occur at Mars. Hara et al (2018) also highlighted the role of the crustal magnetic field in the local increase of this precipitating flux. Hara et al (2018) also highlighted the role of the crustal magnetic field in the local increase of this precipitating flux.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, the dynamic pressure compresses Mars' magnetosphere and favors the acceleration and precipitation of the planetary picked up ions. Also, the presence of crustal magnetic fields (e.g., Acuña et al, ) can also influence locally the precipitating flux as shown by Hara, Luhmann, Leblanc, Curry, Halekas, et al ().…”
Section: Introductionmentioning
confidence: 99%
“…We also restrict our sample of precipitation measurements to those obtained in a solar zenith angle interval between 70° and 130°. Furthermore, in order to avoid the potential influence of the crustal fields (Hara, Luhmann, Leblanc, Curry, Halekas, et al, ; Leblanc et al, ), we also only consider measurements performed when the average magnetic field between 200 and 350 km is less than 60 nT. For each set of solar wind parameters, we calculate the solar wind dynamic pressure, the norm of the solar wind motional electric field defined as E=||Vtrue→SW×Btrue→IMF where B IMF is the interplanetary magnetic field (IMF), the Alfvén Mach number M A = V SW / V A where V A is the Alfvén speed, the solar wind flux defined as F SW = n SW V sw and the pickup O + gyroradius in the solar wind Rg=mOVSWsinθconeitalicqBIMF, where m O is the mass of an O + ion, θ cone is the angle between the IMF direction and the Mars solar Origin (MSO) X axis, and q is the electron charge value.…”
Section: Upstream Solar Wind Conditions and Planetary Coveragementioning
confidence: 99%